The scroll and the marble : studies in reading and reception in Hellenistic poetry - Bing, Peter (University of Michigan Press, 2009)
One of the most prominent figures in American Hellenistic poetry scholarship, Peter Bing has long served as a model for acute criticism and careful reading. He has a marvelous ability to make readers rethink their preconceptions; his work is always beautifully argued and documented and his writing style is a pleasure to engage with. --Benjamin Acosta-Hughes, Ohio State University While people of previous ages relied on public performance as their chief means of experiencing poetry, the Hellenistic age developed what one may term a culture of reading. This was the first era in which poets consciously shaped their works with an eye toward publication and reception not just on the civic stage but in several media--in performance, on inscribed monuments, in scrolls. The essays in Peter Bing's collection explore how poetry accommodated various audiences and how these audiences in turn experienced the text in diverse ways. Over the years, Bing's essays have focused on certain Hellenistic authors and genres--particularly on Callimachus and Posidippus and on epigram. His themes, too, have been broadly consistent. Thus, although the essays in The Scroll and the Marble span some twenty years, they offer a coherent vision of Hellenistic poetics as a whole. Peter Bing is Professor of Classics at Emory University and editor, most recently, of the Companion to Hellenistic Epigram: Down to Philip (coedited with Jon Steffen Bruss). Jacket illustration: Film still from Mr. Smith Goes to Washington, directed by Frank Capra, Columbia Pictures 1939. Courtesy of Sony Pictures.